How terrorism is wrong - Held, Virginia (Oxford University Press, 2008)
How Terrorism is Wrong collects articles by Virginia Held along with much new material. It offers a moral assessment of various forms of political violence, with terrorism the focus of much of the discussion. Here and throughout, Held examines possible causes discussed, including the connection between terrorism and humiliation. Held also considers military intervention, conventional war, intervention to protect human rights, violence to prevent political change, and the status and requirements of international law. She looks at the cases of Rwanda, Kosovo, Iraq, and the Israeli/Palestinian conflict. Finally, she explores questions of who has legitimate authority to engage in justifiable uses of violence, whether groups can be responsible for ethnic violence, and how the media should cover terrorism